Approaches in Mathematical Modeling of Wind Turbines; Encyclopedia of Renewable Energy, Sustainability and the Environment (First Edition) - Razzhivin I. A. Igor Andreevich (2024, 2024)
The introduction of wind turbines into power systems certainly has an impact on their operation. The advanced wind turbines are connected to the grid via power electronic interfaced technologies. Such technologies significantly change the dynamic properties of the power system, including the impact on their modes of operation and stability. Research in this area is carried out mainly by mathematical modeling using various models, which are discussed in this chapter.